The Effects of different nitrogen doses on antioxidant and antimicrobial activity of Stevia (Stevia rebaudiana Bert.) - Atas, Mehmet; Eruygur, Nuraniye; Ucar, Esra; Ozyigit, Yasar; Turgut, Kenan (Cellular and Molecular Biology, 2018)
In this study, the efficiency of the different nitrogen doses (0, 5, 10, 15 and 20 kg ha-1) on biological activity levels (antioxidant and antimicrobial activity) of Stevia rebaudiana Bert. was investigated. In addition, methanol extracts were obtained by maceration method from different doses of fertilizer applied stevia. The components in methanol extracts of plants were determined by gas chromatography-mass spectrometry (GC-MS) method. Antimicrobial activities of stevia extracts were investigated by microdilution method. The antioxidant activity evaluated by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, ferric thiocyanate (FTC), thiobarbituric acid (TBA), reducing power, total phenol content (TPC), and total flavonoid content (TFC) methods. According to the results, the fertilizer doses effects on antimicrobial activity of stevia were not made much difference. But in antioxidant activity, there were some variations in the activity-dependent on fertilizer amount.